Simultaneous MRI of Lung Structure and Perfusion in a Single Breath-hold - Bell, Laura C. (2013)
PURPOSE: To develop and demonstrate a breath-held 3D radial ultrashort echo time (UTE) acquisition to visualize co-registered lung perfusion and vascular structure. METHODS: Nine healthy dogs were scanned twice at 3T. Contrast-enhanced pulmonary perfusion scans were acquired with a temporally interleaved 3D radial UTE (TE = 0.08 ms) sequence in a breath-hold (1 sec time frames over a 33 second breath-hold). The 3D breath-held volume was reconstructed into a time-resolved perfusion datasets, and a composite vascular structure dataset. For structural comparison, a 5 min respiratory-gated 3D radial UTE scan was acquired. Data was analyzed by quantitative metrics and radiologist scoring. RESULTS: Appropriate time-course of contrast was seen in all subjects. Right ventricle to aorta transit times were 7.4 ± 2.0 s. Relative lung enhancement was a factor of 8.4 ± 1.5. Radiologist scoring showed similarly excellent visualization of the pulmonary arteries to the subsegmental level in breath-held (94% of cases) and respiratory-gated (100% of cases) acquisitions (p = 0.33) despite the aggressive under sampling in the breath-held scan. Similar, differentiation of lung tissue and airways was achieved by both acquisition methods. CONCLUSIONS: A time-resolved 3D radial UTE sequence for simultaneous imaging of pulmonary perfusion and co-registered vascular structure is feasible.